Penerapan Jaringan Saraf Tiruan Untuk Bantuan Pengereman Pemain Pada Gim Balapan - Mochamad Halim; Muhammad Aminul Akbar; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Racing game is a video game genre themed around racing event, in which a player compete againts another player or computer to reach the finish line with the shortest clear time. A racing game focused around player reflex, racing technique and track knowledge. It is common for a new player to make many errors, for example driving outside the lane and crashing into the road barrier. For a new player, brake timing is one of the hardest skill to master. Wrong brake timing can cause player to hit the road barrier, or add more to the clear time. A brake assistance is needed to improve a player racing performance by imitating an advanced player brake timing. An advanced player's racing data is recorded, then it is used as training data by an algoritm. ANN (Artificial Neural Network) is an algoritm that can learn the pattern of a data set and have the ability to reduce error, thus this algoritm is acceptable for the brake assist. The metodology used to develop this brake assist is the ANN method. The brake assist system is implemented in the framework of racing game starter kit, an asset package from Unity Asset Store. ANN testing by using blackbox testing validate functionality needs, F1 testing results 0.78 and user acceptance testing shows lower crash count, but increase in total lap time.